2013
DOI: 10.4314/jae.v16i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Crop Farmers’ Perception of and Adaptation to Climate Change in Orlu Agricultural Zone of Imo State, Nigeria

Abstract: Food insecurity is a big challenge which Nigeria is currently battling with. This is compounded by the negative effects of climate change on agricultural production, and by extension, rural development. This work was therefore designed to ascertain crop farmers' perception of, and adaptation to climate change in Orlu agricultural zone of Imo State. The objectives of the study were to: assess farmers' level of awareness of elements of climate change, ascertain the extent farmers perceived climate change in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
2
3
0
2
Order By: Relevance
“…Our results also showed that lack of rains, violent winds and high temperatures are the main factors identified by the producers; which affect the production of cashew. Similar famers perceptions were reported by many studies: Zimbabwe (Moyo et al, 2012); Zambia (Nyanga et al, 2011); Uganda (Kisauzi et al, 2012); Nigeria (Ugwoke et al, 2012); Ghana (MacCarthy and Vlek, 2012); South Benin (Yabi and Afouda, 2012) and Northwest of Benin with yam producers. According to Ayanlade et al (2010), this result was expected because the rainfall is the most important climatic factor affecting agricultural activities in the tropics.…”
Section: Determinants Of the Adoption Of Adaptation Strategy By Produsupporting
confidence: 82%
“…Our results also showed that lack of rains, violent winds and high temperatures are the main factors identified by the producers; which affect the production of cashew. Similar famers perceptions were reported by many studies: Zimbabwe (Moyo et al, 2012); Zambia (Nyanga et al, 2011); Uganda (Kisauzi et al, 2012); Nigeria (Ugwoke et al, 2012); Ghana (MacCarthy and Vlek, 2012); South Benin (Yabi and Afouda, 2012) and Northwest of Benin with yam producers. According to Ayanlade et al (2010), this result was expected because the rainfall is the most important climatic factor affecting agricultural activities in the tropics.…”
Section: Determinants Of the Adoption Of Adaptation Strategy By Produsupporting
confidence: 82%
“…Prominent among those strategies the majority of them employed were: use of fertilizer (97.20%); planting eggplant early (with the first rainfall) (96.30%), crop rotation (93.50%), mixed cropping, planting eggplant in a well-drained soil and treating seed with wood ash before planting (91.70% each), and treating seed with fungicides prior to planting (90.70%). In line with the findings [10] reported that farmers practiced adjustment of planting dates (early planting or late planting) in order to adapt to disease effects on crops. This strategy targets at…”
Section: Knowledge Of Eggplant Farmers On Bacterial Wilt Diseasesupporting
confidence: 85%
“…Selon les producteurs, les variations de la pluviométrie et de la température sont les principales manifestations de ces changements du climat. Ces mêmes manifestations ont été évoquées en Zambie (Nyanga et al, 2011) au Nigéria (Ugwoke et al, 2012) et même dans une région du Nord Benin . Selon Yabi et Afouda (2012), la perception des changements climatiques varie au sein des populations selon leurs caractéristiques sociodémographiques.…”
Section: Discussionunclassified